2019
DOI: 10.1186/s12864-019-5487-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparative transcriptome analysis of the novel obligate methanotroph Methylomonas sp. DH-1 reveals key differences in transcriptional responses in C1 and secondary metabolite pathways during growth on methane and methanol

Abstract: BackgroundMethanotrophs play an important role in biotechnological applications, with their ability to utilize single carbon (C1) feedstock such as methane and methanol to produce a range of high-value compounds. A newly isolated obligate methanotroph strain, Methylomonas sp. DH-1, became a platform strain for biotechnological applications because it has proven capable of producing chemicals, fuels, and secondary metabolites from methane and methanol. In this study, transcriptome analysis with RNA-seq was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…It has been found that the expression of the serine cycle was more activated on methanol and deletion of PPi-PFK showed more defects on this pathway, suggesting the operation of a functional serine cycle. In agreement with this observation, when shifting the substrate from methane to methanol, our current studies showed the activation of serine cycle on methanol-grown for energy regulation [10,16,18], while the serine cycle only carries negligible flux for growth on methane [8]. In summary, those results demonstrated the impact of pfk knockouts on the metabolic phenotype is more expressive and also showed to have a different influence on the metabolism of grown on methane and methanol.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It has been found that the expression of the serine cycle was more activated on methanol and deletion of PPi-PFK showed more defects on this pathway, suggesting the operation of a functional serine cycle. In agreement with this observation, when shifting the substrate from methane to methanol, our current studies showed the activation of serine cycle on methanol-grown for energy regulation [10,16,18], while the serine cycle only carries negligible flux for growth on methane [8]. In summary, those results demonstrated the impact of pfk knockouts on the metabolic phenotype is more expressive and also showed to have a different influence on the metabolism of grown on methane and methanol.…”
Section: Discussionsupporting
confidence: 90%
“…On methane, the expression level of pmo along with xoxF showed a similar expression pattern when pfk was removed. Our previous study suggested that xoxF could contribute to the methane oxidation process in type I methanotrophs [18] by formation of an alternative structure of MDH-pMMO association with the binding of XoxF monomer to pMMO [25]. So that, pfk likely serve as regulatory effects to control this structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with this suggestion, our comparative transcriptome analysis of Methylomonas sp. DH-1 showed the extreme upregulation of MEP pathway encoding genes when shifting substrates from methane to methanol [38]. In addition, the pools of pyruvate and G3P, precursors for the MEP pathway, were approximately 150 and 30-fold higher than that of the acetyl-CoA pool, suggesting that the MEP pathway in methanotrophs is a suitable route to produce isoprenoid-related products [39].…”
Section: Isoprenoid Biosynthesis Via Mep Pathwaymentioning
confidence: 99%
“…Similarly, a comparative transcriptome analysis was utilized in Methylomonas sp. DH-1 to explore the roles of secondary metabolite pathways during growth on CH 4 and methanol (Nguyen et al, 2019). However, there is no systematical research on M. buryatense 5GB1 under different CH 4 /O 2 ratios.…”
Section: Introductionmentioning
confidence: 99%